On the specific filtration mechanism of a mesoporous silica membrane, prepared with non-connecting parallel pores - Boissière, Cédric; Martines, Marco U. [UNESP]; Larbot, André; Prouzet, Eric (Elsevier, 2005)
We report the singular filtration properties of an ultrafiltration membrane made with mesoporous silica that exhibits cylindrical pores aligned mostly normal to the support. This membrane supported on tubular commercial macroporous alumina supports was prepared by the interfacial growth mechanism between stable silica-surfactant hybrid micelles made of the association of silica oligomers with polyethyleneoxide-based (PEO) surfactants and sodium fluoride, a well-known silica condensation catalyst [Boissière et al., An ultrafiltration membrane made with mesoporous MSU-X silica, Chem. Mater. 15 (2003) 460-463]. It appears that the combined effect of the silica nature of the membrane, whose surface charge can be easily adjusted by changing the pH and the non-connected cylindrical shape of the pores provides a new behavior in the retention properties, as proved by the filtration of polyoxyethylene polymers (PEO) with different molecular weights. Depending on the filtration conditions, a rejection rate of 80% and a steep cut-off at 2000 Da can be obtained or, on the reverse, polymers three times bigger than the pore diameter can diffuse through the membrane. This new filtration mechanism, which opens up new modes of separation modes, is explained in the light of both topology of the porous network and pH-dependent interactions between PEO polymers and silica porous media. © 2004 Elsevier B.V. All rights reserved.
Keywords: Membrane; Mesoporous; Silica; Surfactants; Ultrafiltration; Catalysts; Molecular weight; Polyethylene oxides; Polymeric membranes; Porosity; Sodium compounds; Surface active agents; Interfacial growth; Mesoporous silica membranes; Retention; Ultrafiltration membranes; Filtration; aluminum oxide; fluoride sodium; macrogol; oligomer; silicon dioxide; surfactant; membrane structure; membrane technology; porosity; ultrafiltration; artificial membrane; catalyst; filtration; membrane permeability; micelle; pH; polymerization; priority journal; separation technique